Pengaruh Motivasi dan Kompetensi Terhadap Kinerja Pegawai Pada Kantor Samsat Kota Jambi - Atikah, Atikah; AS, Sakinah; Iskandar, Fadil (Universitas Batanghari Jambi, 2024)
The aim of this research is to determine the simultaneous influence of motivation and competence on performance at the Jambi City Samsat Office. The method used is descriptive research using survey techniques, with a quantitative analysis approach and using non-parametric statistics. The research sample consisted of 76 respondents. The research results show that motivation and competency factors have a positive and significant influence on employee performance at the Jambi City Samsat Office. The simultaneous influence of motivation and competence on performance is 35.7%. Motivational factors have the greatest contribution to employee performance at the Jambi City Samsat Office.